Analysis of characteristics of movement disorders in patients with anti-N-methyl-D-aspartate receptor encephalitis - Li, Hongmei; Chen, Jiajie; Zhou, Pinyi; Meng, Qiang (Frontiers in Neurology, 2024)
Objective Movement disorders (MDs) are common in anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis but are poorly studied. This study aimed to investigate the clinical characteristics of MDs and the clinical differences between patients with and without MDs in anti-NMDAR encephalitis. Methods A retrospective study was conducted on patients with anti-NMDAR encephalitis who were first diagnosed and treated in the First People’s Hospital of Yunnan Province from January 2017 to September 2022. According to the presence or absence of MDs, all patients were divided into two groups, and the clinical manifestations, auxiliary examinations, and prognosis of the two groups were compared. Patients in the MDs group were further subgrouped by different ages (<12 years, 12–17 years, and ≥ 18 years) and genders, and the prevalence of each MD was compared in different age and gender groups. Results (1) In our study there were 64 patients, of whom 76.6% (49/64) presented with MDs; the median age of onset in patients with MDs was 21 (15,35) years and 65.3% (32/49) were female. The three most common MDs were orofacial dyskinesia (OFLD) (67.3%), dystonia (55.1%), and stereotypies (34.7%). Patients <12 years were more likely to experience chorea than patients in other age groups (p = 0.003). (2) Compared with the non-MDs group, patients in the MDs group showed higher rates of prodromal manifestations, autonomic dysfunction, consciousness disorders, as well as pulmonary infection and gastrointestinal dysfunction (all p < 0.05). Peripheral blood neutrophil to lymphocyte ratio (NLR) (p = 0.014), the proportion of cerebrospinal fluid (CSF) NMDAR antibody titers ≥1:32 (p = 0.047), ICU admission rate (p = 0.04), length of stay (p = 0.007), maximum mRS score in the course of disease (p = 0.001) and mRS score at discharge (p = 0.006) in the MDs group were significantly higher than the non-MDs group. Conclusion MDs associated with anti-NMDAR encephalitis were predominantly hyperkinetic. Chorea occurred more commonly in patients aged <12 years. Patients with MDs were prone to autonomic dysfunction, consciousness disorders, pulmonary infection, and gastrointestinal dysfunction; they had more intense inflammation, more severe disease, and a poorer short-term prognosis.